The measurement of Gear Transmission Error as an NVH indicator: Theoretical discussion and industrial application via low-cost digital encoders to an all-electric vehicle gearbox. (15th September 2018) - Palermo, Antonio; Britte, Laurent; Janssens, Karl; Mundo, Domenico; Desmet, Wim
Highlights: TE is accurately measured by the Elapsed Time Method (ETM) and low-cost digital encoders. This method substantially improves maximum speed and ease of instrumentation. A validation with the traditional Direct Method is provided through a precision gear test rig. The ETM is applied to the industrial case of a full-electric car gearbox. Robustness of the method is proven and TE is found to be a useful NVH indicator. Abstract: Gear Transmission Error (TE) is often considered as the main cause of gear whine. TE represents the difference between the perfectly kinematic transmission of motion and the one actually achieved. TE vibrations are extremely small and pose significant measurement challenges. This article demonstrates how low-cost digital encoders can be successfully used together with the Elapsed Time Method to simplify TE measurement with respect to the traditional Direct Method. A precision gear pair test rig is exploited to compare the two methods from a theoretical and an experimental point of view. Following the observations drawn from such comparison, a measuring chain is set up to validate the proposed procedure on a real case all-electric vehicle gearbox. It is shown how TE represents a useful gearbox NVH indicator and how it can be used to support gear microgeometry design.